Overview of Ionic Liquids Used as Working Fluids in Absorption Cycles - Khamooshi, Mehrdad; Parham, Kiyan; Atikol, Ugur (Sage Publications Ltd, 2013)
The cycle performance of refrigeration cycles depends not only on their configuration, but also on thermodynamic properties of working pairs regularly composed of refrigerant and absorbent. The commonly used working pairs in absorption cycles are aqueous solutions of either lithium bromide water or ammonia water. However, corrosion, crystallization, high working pressure, and toxicity are their major disadvantages in industrial applications. Therefore, seeking more advantageous working pairs with good thermal stability, with minimum corrosion, and without crystallization has become the research focus in the past two decades. Ionic liquids (ILs) are room-temperature melting salts that can remain in the liquid state at near or below room temperature. ILs have attracted considerable attention due to their unique properties, such as negligible vapor pressure, nonflammability, thermal stability, good solubility, low melting points, and staying in the liquid state over a wide temperature range from room temperature to about 300 degrees C. The previously mentioned highly favorable properties of ILs motivated us for carrying out the present research and reviewing the available ILs found in the literature as the working fluids of absorption cycles. Absorption cycles contain absorption heat pumps, absorption chillers, and absorption transformers.
Keywords: Thermodynamic Analysis; Refrigeration System; Vapor-Pressure; Water; Dimethylphosphate; Performances; Simulation; Binary; Pairs